2021
DOI: 10.33963/kp.15697
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the short-term safety and efficacy of transcarotid and transfemoral access routes for transcatheter aortic valve implantation

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
(44 reference statements)
2
15
0
Order By: Relevance
“…Our previously published data suggest that transcarotid access is comparable in outcomes to TF in properly selected patients and can be safely used as the first-choice alternative access in patients in whom the TF approach is not feasible [3]. In our experience, it is also safe to use local anesthesia as suggested in previously published studies [11].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our previously published data suggest that transcarotid access is comparable in outcomes to TF in properly selected patients and can be safely used as the first-choice alternative access in patients in whom the TF approach is not feasible [3]. In our experience, it is also safe to use local anesthesia as suggested in previously published studies [11].…”
Section: Discussionsupporting
confidence: 69%
“…The current paper provides long term outcomes with routine follow-up with carotid duplex ultrasound (DUS) of all patients treated with TC-TAVI in a large academic institution where TC is the preferred alternative access when TF is not feasible. This is a long-term extension of our previously published data with systematic follow-up with carotid ultrasound [1][2][3].…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…All SE THVs belonged to the Medtronic CoreValve family (Medtronic, Minneapolis, MN, USA). Almost all remaining cases benefited from the Edwards SAPIEN family THVs (Edwards Lifesciences, Irvine, CA, USA), except one, reported by Hudziak et al, in which an Abbott Portico THV (Abbott Vascular, Santa Clara, CA, USA) was implanted ( 24 ). 70.8% of interventions were performed via the left common carotid artery (CCA).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies reported the incidence of PPM implantation ( 11 , 20 , 22 24 , 26 , 27 ). There was no significant difference between TC-TAVR and TF-TAVR, either when all 7 studies were included (RR, 1.01, 95% CI, 0.87–1.17, I 2 = 0%, p = 0.94), or in the subgroup of propensity-score matched studies (only data from one study were available, RR, 1.06, 95% CI, 0.88–1.27, p = 0.54; Figures 5A,B ).…”
Section: Resultsmentioning
confidence: 99%